Jizi and His Art in Contemporary China : Unification - Brubaker; David Adam (Springer, 2020)
This interdisciplinary study promotes the thesis that some contemporary Chinese ink artists succeed in using principles of traditional Chinese aesthetics to convey the union of self with nature, others and the universe. The investigation is a case study of the writings and paintings of Jizi, an ink-wash artist in Beijing, who combines images of icy mountains, Tibetan landscapes, cosmic vistas, and enclosures of personal existence. Jiziu2019s success in expressing the unification of these dimensions is confirmed by developing and applying an interpretation of Jing Haou2019s classic description of the authentic image, which resonates with the vitality of nature...